A Novel Barium Chloride-Catalyzed Approach for Direct Conversion of Waste Leaf Biomass to Methyl Butanoate - Haruna Ibrahim; Abubakar M. Ali; Mohammed Danlami Jibrin (Journal of Scientific Insights, 2026)
The transition toward sustainable and circular bioeconomies requires environmentally benign and resource-efficient routes for producing value-added chemicals from renewable feedstocks. This study presents a rapid and novel approach for synthesising methyl butanoate via a barium chloride-catalyzed thermal hydrolytic process using Gmelina arborea leaf biomass as a low-cost lignocellulosic resource. Unlike conventional esterification methods that depend on refined substrates, corrosive catalysts, and extended reaction times, this process operates under mild conditions (80 °C, atmospheric pressure) with short reaction durations (10–50 minutes). Results show that the highest methyl butanoate yield (≈13.52% and ~900 mg/g) is achieved at 10 minutes, demonstrating good reproducibility (RSD ≈ 6%). ANOVA confirms that reaction time significantly influences yield (p < 0.05), with longer durations reducing performance due to competing reactions and equilibrium constraints. Gas Chromatography–Mass Spectrometry (GC–MS) analysis validates ester formation and composition. This work addresses a key research gap by enabling direct conversion of waste biomass into short-chain esters through a simple, rapid, and energy-efficient pathway. The approach aligns with Sustainable Development Goals: SDG 7 (Affordable and Clean Energy) through biofuel development, SDG 9 (Industry, Innovation and Infrastructure) via process innovation, SDG 12 (Responsible Consumption and Production) through biomass valorization, and SDG 13 (Climate Action) by promoting low-carbon processes. Overall, the study establishes a sustainable alternative for ester production with reduced environmental impact and operational complexity.